2022
DOI: 10.1037/hum0000295
|View full text |Cite
|
Sign up to set email alerts
|

Women’s friendships: A basis for individual-level resources and their connection to power and optimism.

Abstract: The study examined how friendships among women in recovery from substance use disorders are related to individual resources (e.g., social support, self-esteem, and hope) and empowerment (e.g., power and optimism). Findings from a path analysis of 244 women in recovery revealed that friendships among women were positively related to individual resources; that is, the stronger the relationships with other women, the higher women perceived their resources to be. Further, individual-level resources mediated the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…This is illustrated in the women's interviews regarding their move out of drug use, their connections to families and their engagement with recovery communities. Similar to findings from other studies (14,24,49), modifying and transforming relationships were common among the women. Building or re-building positive relationships and protecting themselves from negative relationships are important elements of women's recovery from substance use (26).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is illustrated in the women's interviews regarding their move out of drug use, their connections to families and their engagement with recovery communities. Similar to findings from other studies (14,24,49), modifying and transforming relationships were common among the women. Building or re-building positive relationships and protecting themselves from negative relationships are important elements of women's recovery from substance use (26).…”
Section: Discussionsupporting
confidence: 89%
“…Women’s sense of self is tied to the relationships they nurture or abandon as they move through life. As Guerrero et al have shown, developing and maintaining empowering relationships are important for women in recovery as they can support and encourage improvements in psychological and physical well-being ( 14 ). The importance of social interactions and relationships has the potential to encourage connectedness and a sense of belonging to something that helps shape an individual’s recovery ( 15 ).…”
Section: Introductionmentioning
confidence: 99%